Analytical Method Development and Validation of RP-HPLC Method for Estimation of Escitalopram in Bulk and Pharmaceutical dosage form - Khedkar, Shital; Barge, Vijaya (Journal of Neonatal Surgery, 2025)
Objective: To develop and validate the RP-HPLC method for the estimation of an antidepressant drug Escitalopram Methods: A Phenomenex C-18, 250 mm x 4.6 mm, 5 µm, and a mobile phase made of 0.05% OPA in water: methanol (40:60 v/v) were used for the chromatographic separation. The detection was performed at 238 nm using a 20 μl injection and a flow rate of 1 ml/min. According to ICH Q2 (R1) requirements, the method was validated using a variety of factors, including linearity, precision, accuracy, and robustness. Results: The retention time was observed at 2.70 min. The method was found to be linear with a correlation coefficient (r²) of 0.9997. Conclusion: This approach was proven to be quick, easy, cost-effective, and run time-efficient.The validated parameters manifest that the method is reliable, linear, accurate, and precise, as well as robust with minor variations in chromatographic parameters